2012
DOI: 10.1107/s0108270111054205
|View full text |Cite
|
Sign up to set email alerts
|

2-Ammonio-5-chloro-4-methylbenzenesulfonate, its 1-methyl-2-pyrrolidone and dimethyl sulfoxide monosolvates and a corrected structure of 2,2′-(1,4-phenylene)di(4,5-dihydroimidazolium) bis(4-aminobenzenesulfonate) dihydrate

Abstract: 2-Ammonio-5-chloro-4-methylbenzenesulfonate, C(7)H(8)ClNO(3)S, (Ia), is an intermediate in the synthesis of lake red azo pigments. The present structure determination from single-crystal data confirms the results of a previous powder diffraction determination [Bekö, Thoms, Brüning, Alig, van de Streek, Lakatos, Glaubitz & Schmidt (2010). Z. Kristallogr. 225, 382-387]. The zwitterionic tautomeric form is confirmed. During a polymorph screening, two additional pseudopolymorphs were obtained, viz. 2-ammonio-5-chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…For structure solutions the starting molecular geometry for 1, 3 and 4 was taken from the recently determined single-crystal structure of 2 [7] and the substituents were correspondingly modified with Mercury 3.0 [27]. A zwitterionic form, as found for 2, was assumed, but at this stage, very similar results would have been obtained with the neutral tautomeric form as well.…”
Section: Structure Determinations Of 13 and 4 From Xrpd Datamentioning
confidence: 99%
See 1 more Smart Citation
“…For structure solutions the starting molecular geometry for 1, 3 and 4 was taken from the recently determined single-crystal structure of 2 [7] and the substituents were correspondingly modified with Mercury 3.0 [27]. A zwitterionic form, as found for 2, was assumed, but at this stage, very similar results would have been obtained with the neutral tautomeric form as well.…”
Section: Structure Determinations Of 13 and 4 From Xrpd Datamentioning
confidence: 99%
“…In 2010 we investigated the crystal structure and the tautomeric state of 2 using X-ray powder diffraction (XRPD), IR and solid-state NMR spectroscopy. All methods revealed the zwitterionic tautomer of 2 [6,7]. In 1985 solid-state NMR investigations indicated that 2-aminobenzenesulfonic acid ( Figure 1, R 1 = R 2 = H) and 2-amino-5-methylbenzenesulfonic acid (R 1 = H, R 2 = CH 3 ) are zwitterionic, but the data on 2-amino-5-nitrobenzenesulfonic acid (R 1 = H, R 2 = NO 2 ) were interpreted as an indication for the neutral amine tautomer in solid state [8].…”
Section: Introductionmentioning
confidence: 99%